Examining the impact of weight loss and exercise on pelvic organ prolapse (POP) management - Moskal, Bartosz; Bednarczyk, Małgorzata Maria (Quality in Sport, 2024)
Introduction: Pelvic organ prolapse is a descent of pelvic organs such as the bladder, cervix, apex of the vagina, and rectum which create herniation and slide into the direction of the vagina entrance. Pelvic prolapse is caused by ligament and muscle weakness, and its risk increases with age, parity, and obesity. Proper exercise and weight loss can be a key component of pelvic prolapse management, especially in the I-III stages. Those interventions may decrease the need for pelvic surgery and the risk of complications that can arise from it. Purpose of the study: This study aimed to explore the effectiveness of weight loss and exercise on pelvic organ prolapse (POP) symptoms and staging. Materials and methods: A comprehensive analysis of research papers available on PubMed, and Google Scholar was undertaken using the keywords: ‘weight loss pelvic prolapse’, ‘exercise in pelvic prolapse’, ‘pelvic floor dysfunction’, ‘pelvic floor muscle training’, ‘hypopressive exercises’, ‘biofeedback prolapse’ Results: Conventional weight loss does not reduce the intensity of the pelvic prolapse symptoms. However, weight loss that is achieved via bariatric surgery is effective in reducing symptoms arising from pelvic organ prolapse. Furthermore, the bigger the amount of weight loss the greater improvement in symptoms. Pelvic floor muscle training showed improvement in symptoms and in the staging of pelvic organ prolapse. Hypopressive exercises are not as effective as pelvic floor muscle training. Biofeedback and supervised exercises are helpful in proper exercise execution, and thus may improve the strength of the pelvic floor muscles.